KEDAULATAN NEGARA DALAM KERANGKA HUKUM INTERNASIONAL KONTEMPORER - Sigit Riyanto (Yustisia, 2012)
AbstractThis research aimed at comprehensively analize the concept of State sovereignty and its application in the contemporary international law. In this research the concept of State sovereignty and relevant rules of international law have been analysed accordingly. Legal materials that thoroughly considered and studied in the context of this research were relevant international rules and facts embodied in international cus- toms, general principles of law, international treaties, conventions, declarations and decisions of interna- tional organisation, recommendations, guiding principles, plan of actions, executive committee decisions, reports, academic publications, proceedings and working papers. Legal materials obtained were classified systematically and interptreted and evaluated thouroughly. The formulation concerning the the relevant facts and international legal frameworks pertainingto the concept of sovereignty based upon interpretation and evaluation of the existing legal materials. Eventually, the concept of sovereignty in the contemporary international society could be revealed accordingly. The State sovereignty is relational and open concept; not an insular or narrow and closed concept. A visionary discourse is needed to reinvent the valid interpre- tation of sovereignty in the framework of interdependence among States in the present international sys- tem. Sovereignty shall be interpreted as responsibility of the national authority. In this context State as an agent and manifestation of people sovereignty has the primary responsibility to protect, respect and fulfill the citizen rights accordingly and accountable to the international society. AbstrakPenelitian ini dilakukan untuk melakukan kajian mendalam dan akurat tentang konsep kedaulatan negara dan penerapannya dalam kerangka hukum internasional kontemporer. Bahan kajian utama penelitian ini adalah keputusan dan fakta-fakta hukum internasional yang relevan,  yang tertuang dalam hukum internasional kebiasaan, prinsip-prinsip umum hukum, perjanjian internasional, konvensi, deklarasi dan keputusan-keputusan organisasi internasional, rekomendasi organisasi internasional, prinsip-prinsip panduan, buku panduan, rencana aksi, keputusan komite eksekutif, laporan, publikasi ilmiah, proceedings seminar, dan kertas kerja. Setelah dilakukan klasifikasi dan sistematisasi bahan penelitian, berikutnya dilakukan interpretasi dan evaluasi. Berdasarkan interpretasi dan evaluasi tersebut, dilanjutkan dengan preskripsi untuk merumuskan kejelasan tentang konteks situasi faktual dan kerangka hukum  internasional yang relevan. Pada akhirnya dapat diketahui konsep kedaulatan negara dalam masyarakat internasional terkini. Kedaulatan bersifat relasional dan terbuka; bukan suatu konsep yang “insular” atau sempit dan tertutup. Suatu wacana visioner diperlukan untuk merekonstruksi kedaulatan negara dalam kerangka interdependensi antar negara dalam sistem internasional terkini. Kedaulatan negara harus dimaknai sebagai tanggung jawab otoritas nasional. Dalam konteks ini negara sebagai agen dan manifestasi dari kedaulatan rakyat, bertanggungjawab untuk melindungi, menghormati dan memenuhi hak-hak warganya serta harus mempertanggungjawabkan mandatnya kepada masyarakat internasional.